Reasons for the reluctance of Arabic language teachers to use educational technology in teaching the Arabic language at the secondary stage from the point of view of Arabic language teachers in the Ministry of Education in the State of Kuwait - فاطمة الهاجري (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of the study was to analyse the reasons for the reluctance of Arabic language teachers to use educational technology in teaching the Arabic language to the secondary stage in the State of Kuwait, and to measure differences according to some personal variable. The researcher adopted the descriptive survey method and used a questionnaire of her own design that included thirty items divided into three. The axes (obstacles related to teachers, obstacles related to learners, obstacles related to content) were distributed randomly to (360) Arabic language teachers at the secondary stage. The results of the study indicated that there was no statistical significance in the sample members’ assessment of the reasons for the reluctance of Arabic language teachers to teach The use of educational technology according to their personal variables, which are (gender, educational qualification, teaching experience). In addition, the results revealed that a significant factor affecting the reluctance of male and female teachers of the Arabic language in the secondary stage to use educational technology in teaching is the lack of availability of modern equipment and devices in the school with a high average of ( 3.68), and the classrooms were overcrowded with learners with a high average of (3.71), and based on the results, the study presented some recommendations.